Grayscale and Color Doppler Features of Testicular Lymphoma. (1st June 2015) - Bertolotto, Michele; Derchi, Lorenzo E.; Secil, Mustafa; Dogra, Vikram; Sidhu, Paul S.; Clements, Richard; Freeman, Simon; Grenier, Nicolas; Mannelli, Lorenzo; Ramchandani, Parvati; Cicero, Calogero; Abete, Luca; et al.
Abstract : Pooled data from 16 radiology centers were retrospectively analyzed to seek patients with pathologically proven testicular lymphoma and grayscale and color Doppler images available for review. Forty‐three cases were found: 36 (84%) primary and 7 (16%) secondary testicular lymphoma. With unilateral primary lymphoma, involvement was unifocal (n = 10), multifocal (n = 11), or diffuse (n = 11). Synchronous bilateral involvement occurred in 6 patients. Color Doppler sonography showed normal testicular vessels within the tumor in 31 of 43 lymphomas (72%). Testicular lymphoma infiltrates through the tubules, preserving the normal vascular architecture of the testis. Depiction of normal testicular vessels crossing the lesion is a useful adjunctive diagnostic criterion.